Hitler's foreign executioners : Europe's dirty secret - Hale, Christopher (HarperPress, 2011)
'Hitler's Foreign Executioners' reveals for the first time Heinrich Himmler's masterplan for Europe: an SS empire that would have no place for either the Nazi Party or Adolf Hitler. Instead, Himmler planned to recruit tens of thousands of 'Germanic' peoples to build an 'SS Europa'